REHABILITASI TERHADAP PENGGUNA DAN KORBAN PENYALAHGUNAAN NARKOTIKA DALAM KONSEP PEMIDANAAN DI INDONESIA (STUDI KASUS PUTUSAN DI PENGADILAN NEGERI PURWOKERTO) - Sitorus, Tofri Dendy Baginda; Gultom, Maidin; Marbun, Jaminuddin (JURNAL PROINTEGRITA, 2020)
The application of legal sanctions against perpetrators of narcotics crimes can be subject to rehabilitation sanctions. The purpose of punishment in narcotics crime as stipulated in Article 127 of Act Number 35 of 2009 must be carried out selectively regarding whether the perpetrator is a user or distributor. The conflict or norm conflict against the Law occurs in Article 127 where in Article 127 paragraph (1) the Judge can convict a narcotics abuser while in paragraph (2) and paragraph (3) it is stated that the Judge must rehabilitate addicts and victims of narcotics abuse. But in fact not all judges provide rehabilitation decisions. As happened in the Purwokert District Court.. The research conducted is normative legal research with the nature of descriptive analysis. This study used secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. Based on the results of the study, it was found that the determination of sanctions against narcotics addicts, whether to impose criminal sanctions or sanction rehabilitation, this determination was in the hands of the judge. in accordance with the provisions of Article 127 and Article 103 of Law Number 35 of 2009. In the Indonesian criminal system, a double track system is known where the criminal system consists of criminal sanctions (sanctions) and sanctions for action (maatregel) so that based on article 54 of the Law Number 35 of 2009 for users and victims of narcotics abuse, medical and social rehabilitation is required.